Selective depletion of regulatory T cells enhances the immunogenicity of a recombinant-based vaccine against Sporothrix spp - Batista-Duharte, Alexander; Téllez-Martínez, Damiana; Portuondo, Deivys Leandro; Carlos, Iracilda Zeppone (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Regulatory T cells (Tregs) have been shown to limit the protective immune response against pathogenic species of the fungus Sporothrix spp, the causal agent of sporotrichosis. However, the specific function of Tregs during vaccination against these fungi is known. Methods We evaluated the effect of Tregs depletion on the immunogenicity of an experimental recombinant anti-Sporothrix vaccine, using the DEREG mice. In this model, only Foxp3(+) Tregs express eGFP and diphtheria toxin (DT) receptors, and transient Tregs depletion is achieved by DT administration. Results Tregs depletion enhanced the frequency of specific IFNγ+ T cells (Th1 lymphocytes) and cytokine production after either the first or second vaccine dose. However, depletion of Tregs during the second dose caused greater stimulation of specific Th1 lymphocytes than depletion during the first dose. Similarly, the highest production of IgG, IgG1, and IgG2a anti rSsEno antibody was detected after Tregs depletion during boost immunization compared to the other immunized groups. Importantly, vaccine immunogenicity improvement after Tregs depletion also had an impact on the more efficient reduction of fungal load in the skin and liver after the challenge with S. brasiliensis in an experimental infection model. Interestingly, the reduction in fungal load was greatest in the Tregs depleted group during boosting. Discussion Our results illustrate that Tregs restrict vaccine-induced immune response and their transient depletion could enhance anti-Sporothrix vaccine immunogenicity. Further studies are required to elucidate whether Tregs depletion may be a way to improve the efficacy of vaccination against Sporothrix spp.